Strategi Komunikasi Persuasif pada Konten Self-Development di Akun Instagram @ananzaprili - Diah Retno Ningsih (Asosiasi Peneliti dan Pengajar Ilmu Sosial Indonesia, 2025)
In today's digital age, social media has become an effective platform for conveying messages and influencing audience behavior, with Instagram being a prime example. Persuasive communication is a key strategy for delivering messages that can motivate, inspire, and shift the mindset of audiences. One content creator who actively shares self-development messages is @ananzaprili, who employs persuasive communication techniques to capture audience attention. This research aims to analyze the application of persuasive communication techniques in self-development content published by content creator @ananzaprili. Employing a descriptive qualitative method and drawing upon Carl Hovland's persuasive communication theory, this study identifies various persuasive strategies such as association, integrity, rewards/incentives, arrangement, and red-herring. The persuasive communication strategies implemented by @ananzaprili enhance audience engagement and encourage positive behavioral changes related to self-development. Furthermore, the use of engaging language that fosters active involvement with followers is a key factor in the success of this strategy.